2014
DOI: 10.1080/21650020.2014.906907
|View full text |Cite
|
Sign up to set email alerts
|

Pedestrian and bicyclist motivation: an assessment of influences on pedestrians’ and bicyclists’ mode choice in Mt. Pleasant, Vancouver

Abstract: The majority of short distance travel in North America is completed by single occupancy vehicles. Substituting walking and bicycling for these trips would reduce energy use and environmental pollution, while improving quality of life. Therefore, understanding influences on non-automotive travel behavior is crucial. Researchers and planners have touted specific factors for encouraging walking and biking, but the body of work remains fragmented. Previous studies have focused on a smaller number of factors and mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 33 publications
(59 reference statements)
0
9
0
Order By: Relevance
“…Trip distance appears to play a key role as it is one of the variables that makes bicycle use prohibitive for long distance travel [31], and attractive for shorter routes [32,33], for example, in the Netherlands where 25% of the total trips realized per person per day are made by bicycle. This share went up to 33% when considering that the trips were no longer than 7.5 km, and even up to 44% when the trips were between 1 km and 2.5 km [26].…”
Section: Introductionmentioning
confidence: 99%
“…Trip distance appears to play a key role as it is one of the variables that makes bicycle use prohibitive for long distance travel [31], and attractive for shorter routes [32,33], for example, in the Netherlands where 25% of the total trips realized per person per day are made by bicycle. This share went up to 33% when considering that the trips were no longer than 7.5 km, and even up to 44% when the trips were between 1 km and 2.5 km [26].…”
Section: Introductionmentioning
confidence: 99%
“…But design clearly has an important role to play in supporting and encouraging cycling. As one recent study found, the surveyed cyclists ranked a visually appealing environment as a highly motivating factor in their choice to cycle (Guinn & Stangl, 2014).…”
Section: Resultsmentioning
confidence: 94%
“…Broadly, personal security concerns for pedestrians or bicyclists include crime, trash, abandoned properties, poor building maintenance, and poor lighting ( 17 , 18 ), but personal security often receives insufficient attention from planners ( 19 , 20 ). Older adult, Black residents mentioned a lack of police or security personnel and slow response times as barriers to personal security ( 17 ).…”
Section: Literature Reviewmentioning
confidence: 99%